A bi-level design and operation optimization process applied to an energy centre. Issue 3 (3rd May 2016) - Evins, Ralph
Abstract : This paper presents the methods and results of a bi-level optimization process used to select and size the components of an energy centre as well as to determine their optimal operation. The optimization process used a single-objective optimization of operational control nested within a two-objective optimization of design parameters that minimized capital costs and carbon emissions. Different cases were examined in which the 'credit' assigned for the export of excess electricity to the grid was varied. Results are presented including the overall trade-off front, trends amongst design variables, operational schedules for a particular solution, and aggregated parameters like total energy supplied by each device. Constraints on roof area were critical at the design-level, and complex interactions between demand and supply were identified at the operational level. Comparison of the two cases highlights the impact of the export of excess power to the grid.